Application of nanomaterials in the development of biosensors for food safety and quality control - Azri, Farah Asilah; Sukor, Rashidah; Abu Bakar, Fatimah; Selamat, Jinap (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Nanotechnology contribute to significant impacts in every way in our daily life. Recently, the application of nanotechnology in biosensors has been a trend in developing a highly sensitive, selective, quick response, inexpensive, high volume production, great reliability and miniaturized sensors. High demands on the production of rapid sensors for food safety and quality control purposes are increasingly become the interest for researchers all over the world. This is because, in food sector, the quality of a certain product is based on their periodic chemical and microbilogical analysis. The uses of nanomaterials in biosensors are very promising because they mediate current flow. Surface modification of the electrode based on various nanomaterials including nanoparticle, nanofiber, nanowire and nanotube significantly increase the performance of the biosensor. Ultimately, this implementation will enhance the sensor's sensitivity and stability. This review explores the previous research and development work on nanomaterials-based sensors for food applications.